Investigation of some properties of pet (polyethylene terephthalate) poy yarns containing plasmonic boron nanoparticles additive - Görgün, Didem Ezgi; Kumartaşlı, Sedat; Avinc, Ozan; Atar, Necip (Wydawnictwo Politechniki Łódzkiej, 2022)
In this study, it was aimed to increase the contribution to the national economy based on boron, which creates a competitive advantage in the development of new technological solutions and to expand the use of boron products. It is necessary to create new generation textile fibers with new usage areas of rich boron resources and to acquire boron products with high added value and new production areas for new markets. Technological and scientific developments in the field of nanomaterials are often used in the functionalization and modification of textile fibers. The usage properties and functions of synthetic yarns can be improved by the utilization of nanomaterials and nano-systems. In this study, PET (Polyethylene Terephthalate) POY (Partially Oriented Yarn) yarns containing different amounts of new generation plasmonic nanocomposite particles [functionalized core-shell nanohybrid nanoparticles (TiNPs@amine- functionalized GQDs@BNNS nanohybrid nanoparticles)] were produced via melt spinning process. Then, the strength, elongation, yarn unevenness, degreasing, etc. properties of PET POY yarns containing boron-based nanocomposite were investigated. With this study, it was ensured that boron-based nanocomposite-doped polyester fibers containing a new generation of plasmonic nanoparticles were developed and produced on an industrial scale.
Keywords: boron; boron nitride nanoparticle; graphene quantum dots; titanium nanoparticle; polyester; polyethylene terephthalate; PET; fiber spinning; melt spinning; nanocomposite; POY; bor; nanocząstka azotku boru; grafenowe kropki kwantowe; nanocząstka tytanu; poliester; politereftalan etylenu; przędzenie włókien; przędzenie ze stopu; nanokompozyt; przędza częściowo zorientowana